2020
DOI: 10.3390/ijerph17145061
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impacts of Urban and Transit Planning Scenarios for 2031 on Car Use and Active Transportation in a Metropolitan Area

Abstract: Land use and transportation scenarios can help evaluate the potential impacts of urban compact or transit-oriented development (TOD). Future scenarios have been based on hypothetical developments or strategic planning but both have rarely been compared. We developed scenarios for an entire metropolitan area (Montreal, Canada) based on current strategic planning documents and contrasted their potential impacts on car use and active transportation with those of hypothetical scenarios. We collected and analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Active transportation is either researched as a mode of utilitarian transport or daily commute that benefits environmental sustainability (Duquet and Brunelle 2020;Iamtrakul and Zhang 2014) or as a factor for health (Hu et al 2014;Morency et al 2020). Without differentiating between mobilities, these papers provide no way of analysing mobilities for recreational purposes.…”
Section: Mobilities For and As Recreationmentioning
confidence: 99%
“…Active transportation is either researched as a mode of utilitarian transport or daily commute that benefits environmental sustainability (Duquet and Brunelle 2020;Iamtrakul and Zhang 2014) or as a factor for health (Hu et al 2014;Morency et al 2020). Without differentiating between mobilities, these papers provide no way of analysing mobilities for recreational purposes.…”
Section: Mobilities For and As Recreationmentioning
confidence: 99%
“…King explores how the walkability of communities around transit stops can inform future TOD developments [20]. Morency, after conducting scenario simulations for four different plans in the Montreal metropolitan area, found that TOD areas could reduce walking travel distances by 28% [21]. Nasri studies the impact of the built environment on mode of transportation choice within the context of TOD, using discrete choice models and focusing on the built environment at the origin of trips [22].…”
Section: Introductionmentioning
confidence: 99%